2013
DOI: 10.1177/0960327113497770
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of γ-aminobutyric acid (GABA) transaminase activity contributes to GABA increase in the cerebral cortex of mice exposed to β-cypermethrin

Abstract: The current study investigated the γ-aminobutyric acid (GABA) levels and GABA metabolic enzymes (GABA transaminase (GABAT) and glutamate decarboxylase (GAD)) activities at 2 and 4 h after treatment, using a high-performance liquid chromatography with ultraviolet detectors and colorimetric assay, in the cerebral cortex of mice treated with 20, 40 or 80 mg/kg β-cypermethrin by a single oral gavage, with corn oil as vehicle control. In addition, GABA protein (4 h after treatment), GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…The results of the present study supported the previous theory; there was statistically significant decrease in mean brain GABA concentration of CYP-treated group in comparison to control group. This result is in 29 agreements with Kumar et al [5] & Manna et al, [30] who stated that CYP leading to significant decrease in GABA level. This result is against Han et al [31] who stated that increased level of the GABA was detected in the cerebral cortex of mice exposed to CYP in a dose of (20 mg/kg).…”
Section: Discussionsupporting
confidence: 91%
“…The results of the present study supported the previous theory; there was statistically significant decrease in mean brain GABA concentration of CYP-treated group in comparison to control group. This result is in 29 agreements with Kumar et al [5] & Manna et al, [30] who stated that CYP leading to significant decrease in GABA level. This result is against Han et al [31] who stated that increased level of the GABA was detected in the cerebral cortex of mice exposed to CYP in a dose of (20 mg/kg).…”
Section: Discussionsupporting
confidence: 91%
“…Other paper found that AVM would cause twitching and keep exciting in bees; this may relate to the fact that AVM inhibits the expressions of GAD and GABA-T in the cerebellum (Zhao et al 2014). Besides, deltamethrin and β-cypermethrin could downregulate GABA-T level in the cerebral cortex of rats, which resulting in an increase in GABA level (Ji et al 2003;Han et al 2014). All the evidences mentioned above suggested that AVM would break through the blood-brain barrier, which lead to the increase of GABA through affecting the mRNA expressions of GAD 65 , GAD 67 , and GABA-T in crucian carp's nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…γ-amino butyric acid (GABA) is the brain’s major inhibitory neurotransmitter, and inhibitory neurotransmission abnormalities have been linked to ASD [5661]. There are two major types of GABA receptors, GABAA and GABAB.…”
Section: Neurobiological Basis For Social Deficits In Asdmentioning
confidence: 99%
“…Animal studies have also been performed to further study GABAA in ASD. Enhancement of GABAA action has been shown to reverse behavioral deficits in a mouse model of ASD [61], while reduction in GABAA signaling exacerbates deficits [61]. …”
Section: Neurobiological Basis For Social Deficits In Asdmentioning
confidence: 99%
See 1 more Smart Citation